2013
DOI: 10.5511/plantbiotechnology.12.1127a
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lignocellulose of Erianthus arundinaceus in relation to enzymatic saccharification efficiency

Abstract: Lignin is a major component of the secondary cell walls of vascular plants, and an obstacle in the conversion of plant cell wall polysaccharides into biofuels. Erianthus spp. are large gramineous plants of interest as potential energy sources. However, lignocelluloses of Erianthus spp. have not been chemically characterized. In this study, we analysed lignins, related compounds, enzymatic saccharification efficiencies, and minerals in the ash of the inner and outer parts of the internode, leaf blade and leaf s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 45 publications
2
21
1
1
Order By: Relevance
“…All three organs showed higher enzymatic saccharification efficiency, and in COMT1-KD culm, the efficiency increased up to 123.1% compared with WT. This result was in accordance with the fact that lignin generally inhibits the enzymatic saccharification process (Li et al 2008), although not only lignin but also other factors affect enzymatic saccharification of gramineae lignocellulose (Yamamura et al 2013). …”
Section: Comprehensive Gene Expression Analysis In the Cinnamate/monosupporting
confidence: 73%
See 1 more Smart Citation
“…All three organs showed higher enzymatic saccharification efficiency, and in COMT1-KD culm, the efficiency increased up to 123.1% compared with WT. This result was in accordance with the fact that lignin generally inhibits the enzymatic saccharification process (Li et al 2008), although not only lignin but also other factors affect enzymatic saccharification of gramineae lignocellulose (Yamamura et al 2013). …”
Section: Comprehensive Gene Expression Analysis In the Cinnamate/monosupporting
confidence: 73%
“…Taken together, these data indicated that OsCOMT1 functioned as a 5-HCAld OMT (OsCAldOMT1) in the biosynthetic pathway to syringyl lignin. Recently, because of the increased demand for biobased materials as alternatives to fossil carbon resources, gramineous plants that produce large amounts of inedible lignocellulosic biomass have been drawing attention as potential materials for biofuel and industrial feedstock production (Yamamura et al 2013). Lignocellulose is composed mainly of lignin and polysaccharides.…”
mentioning
confidence: 99%
“…Third, higher plant lignin content may be correlated with higher biomass production. Relatively large graminaceous plants, such as bamboo (Phyllostachys heterocycla) (approximately 14 m tall) and Erianthus (approximately 4.5 m tall) generally have higher lignin content (approximately 26% and 23-28%, respectively) (Higuchi 1957;Itoh 1990;Yamamura et al 2013) than smaller graminaceous plants such as rice (O. sativa, approximately 80 cm tall with ca. 10-15% of lignin content) (Suzuki et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, more than 60% of rice straw is deposited on rice fields (Park et al 2011). In addition, rice is an important model plant for largesized Gramineae bioenergy plants, such as Erianthus, napier grass, and switch grass (Yamamura et al 2013). Hence, many research projects for bioconversion of rice straw to fermentable carbohydrates are on-going in Japan (Park et al 2011).…”
mentioning
confidence: 99%